2019
DOI: 10.1021/acs.jpcb.9b07359
|View full text |Cite
|
Sign up to set email alerts
|

Surface Inhomogeneity of Graphene Oxide Influences Dissociation of Aβ16–21 Peptide Assembly

Abstract: Abnormal peptide assembly and aggregation is associated with an array of neurodegenerative diseases including Alzheimer’s disease (AD). A detailed understanding of how nanostructured materials such as oxidized graphene perturb the peptide assembly and subsequently induce fibril dissociation may open new directions for the development of potential AD treatments. Here, we investigate the impact of surface inhomogeneity of graphene oxide (GO) on the assembly of amyloid-beta Aβ16–21 peptides on GO surfaces with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…However, the exact nature of the bonds between Dau and GO still needs to be determined. We had confirmed that GO@Dau inhibited the aggregation of the Ab peptide using the ThT fluorescence test (He et al, 2019). In the Ab 1-42 -induced cellular model in this study, it was found that, compared with Dau or GO alone, GO@Dau significantly decreased the levels of ROS and MDA in SH-SY5Y cells and significantly up-regulated the cell survival rate as well as the levels of SOD and Nrf2/Keap1 pathway-related proteins.…”
Section: Discussionsupporting
confidence: 66%
“…However, the exact nature of the bonds between Dau and GO still needs to be determined. We had confirmed that GO@Dau inhibited the aggregation of the Ab peptide using the ThT fluorescence test (He et al, 2019). In the Ab 1-42 -induced cellular model in this study, it was found that, compared with Dau or GO alone, GO@Dau significantly decreased the levels of ROS and MDA in SH-SY5Y cells and significantly up-regulated the cell survival rate as well as the levels of SOD and Nrf2/Keap1 pathway-related proteins.…”
Section: Discussionsupporting
confidence: 66%
“…An interesting study on the effect of surface inhomogeneity of GO nanosheets as a potential Aβ dissociation mechanism has also been reported. [ 66 ] The authors of the study showed, using molecular dynamics simulation, that the Aβ peptides tend to bind to the scattered surfaces of oxidized and nonoxidized regions of GO, affecting the self‐assembly of the Aβ peptides. More specifically, it was suggested that the aromatic peptide residues bind to the sp 2 (nonoxidized) regions, whereas the polar residues demonstrate an affinity for the oxidized ones, resulting in the dissociation of the fibrils.…”
Section: Gbms In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Moreover, nanocellulose in the form of nanoparticles, tablets, gas-liquid gel system, and fiber membrane system is widely used in the field of energy storage (Chen et al 2018), wastewater treatment (Tang et al 2019), 3D bioprinting (Dorishetty et al 2020), biosensor (Golmohammadi et al 2017), drug delivery (Salimi et al 2019) and other biological fields. Compared with graphene (Luan, Huynh and Zhou 2016), graphene oxide (He et al 2019), molybdenum disulfide (Gu et al 2016;Gu et al 2017), carbon nanotube (El-Sayed et al 2016), and other 2D nanomaterials, nanocellulose as a carrier material has a lower nanotoxicity, which makes it more widely available. Although nanocellulose and its derivatives have been widely concerned in medicine and biological tissue, the long-term retention of nanocellulose in the human body makes its toxicity study very important due to the lack of cellulose-degrading enzymes in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many the interaction between two-dimensional nanomaterials and biomacromolecules have also been investigated by molecular dynamics simulations. Zhou et al, adopted molecular dynamics simulation (MD) to conduct thorough research on the interfacial properties of two-dimensional nanomaterials and found that graphene (Luan et al 2016), graphene oxide (He et al 2019;Mathesh et al 2016), defective graphene (Gu et al 2019) and other carbon nanomaterials can induce protein and nucleic acid denaturation, which provided theoretical support for the potential nanotoxicity of nanomaterials when used in biological systems. , In this work, Ιβ-cellulose, which is one of the main components of higher plants, was selected to model nanocellulose.…”
Section: Introductionmentioning
confidence: 99%